Isomerization of ribose to ribulose using basic amino acids as a catalyst - Khuwijitjaru, Pramote; Adachi, Shuji (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2023)
In a batch reactor, 0.01 mol/L arginine, lysine, or histidine, which are natural basic amino acids, was used as an environmentally friendly, “green”, catalyst to isomerize 0.2 mol/L ribose to the corresponding ketose, ribulose, at 110 °C. The changes over time in the conversion of ribose, the yield of ribulose, pH, and the absorbance of the reaction mixture at 280 and 420 nm were measured. The yield of ribulose was highest (ca. 8.5 %) when arginine was used as a catalyst, followed by lysine. Ribulose was also produced with histidine, but the yield was very low (ca. 1.5 %). On the other hand, the coloration, which was evaluated by the absorbance of the reaction mixture at 280 and 420 nm, was highest when lysine was used, followed by arginine. Therefore, arginine was the most suitable green catalyst for isomerizing ribose to ribulose among the three basic amino acids tested.